'Sticky' neutrophils, pathergic arthritis, and response to heparin in pyoderma gangrenosum complicating ulcerative colitis. Issue 4 (October 1995) - Dwarakanath, A D; Yu, L G; Brookes, C; Pryce, D; Rhodes, J M
Abstract : Pyoderma gangrenosum is strongly associated with inflammatory bowel disease and exhibits pathergy, occurring at sites of previous minor trauma. A patient is presented with a 21 year history of extensive ulcerative colitis, who developed pyoderma gangrenosum and arthralgia while receiving high dose corticosteroids for active ulcerative colitis. The arthralgia exhibited pathergy affecting particularly the left temporomandibular joint, which was stressed by an asymmetric bite, and the left elbow, which had been fractured many years previously. This prompted the hypothesis that neutrophils in this condition may be marginated, as a result of increased stickiness of either the neutrophil or the vascular endothelium. The introduction of heparin therapy was associated with rapid resolution of the arthralgia, pyoderma gangrenosum, and ulcerative colitis.